Harmine augments electrically evoked dopamine efflux in the nucleus accumbens shell. (January 2013) - Brierley, Daniel I; Davidson, Colin
Harmine is a β-carboline alkaloid and major component of ayahuasca, a traditional South American psychoactive tea with anecdotal efficacy for treatment of cocaine dependence. Harmine is an inhibitor of monoamine oxidase A (MAO-A) and interacts in vitro with several pharmacological targets which modulate dopamine (DA) neurotransmission. In vivo studies have demonstrated dopaminergic effects of harmine, attributed to monoamine oxidase inhibitor (MAOI) activity, however none have directly demonstrated a pharmacological mechanism. This study investigated the acute effects, and pharmacological mechanism(s), of harmine on electrically evoked DA efflux parameters in the nucleus accumbens both in the absence and presence of cocaine. Fast cyclic voltammetry in rat brain slices was used to measure electrically evoked DA efflux in accumbens core and shell. Harmine (300 nM) significantly augmented DA efflux (148±8% of baseline) in the accumbens shell. Cocaine augmented efflux in shell additive to harmine (260±35%). Harmine had no effect on efflux in the accumbens core or on reuptake in either sub-region. The effect of harmine in the shell was attenuated by the 5-HT2A/2C antagonist ketanserin. The MAOI moclobemide (10 µM) had no effect on DA efflux. These data suggest that harmine augments DA efflux via a novel, shell-specific, presynaptic 5-HT2A receptor-dependent mechanism, independent of MAOI activity. A DA-releasing 'agonist therapy' mechanism may thus contribute to the putative therapeutic efficacy of ayahuasca for cocaine dependence.